PENERAPAN PEMBELAJARAN BERBASIS PBL MENGGUNAKAN VIDIO PEMBELAJARAN DALAM MEMFASILITASI PEMAHAMAN KONSEP PERUBAHAN WUJUD ZAT PADA SISWA KELAS 4 SD - Rajagukguk, Ruth Maret Tasya; rhomadhona, wulan; Barokah, Rifqa Gusmida Syahrun; Hermita, Neni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the effectiveness of Problem-Based Learning (PBL) with video media in facilitating fourth-grade students’ understanding of the concept of changes in the state of matter at SDN 184 Pekanbaru. The background of the research stems from the passive participation of students in conventional science learning, where only 30% could answer conceptual questions correctly. The study aims to analyze how PBL-based video learning enhances students’ conceptual grasp through qualitative case study methods. The research involved 24 students divided into four groups, employing three phases: stimulation via silent experiment videos, structured group discussions, and evaluation using student worksheets (LKPD) and presentations. Data were collected through participatory observation, documentation of group discussions, and teacher reflections, then analyzed via data reduction, presentation, and conclusion drawing. Results showed a significant increase in active participation (from 35% to 75%) and conceptual understanding, as evidenced by LKPD scores, with students accurately identifying phenomena like melting ice and sublimating camphor. Despite challenges such as time management and classroom disruptions, the integration of PBL and visual media proved effective in fostering critical thinking and collaboration. The findings align with the NSTA (2022) recommendations for inquiry-based learning and highlight the potential of interactive strategies in elementary science education. This study contributes to the development of innovative teaching methods that bridge theoretical concepts with real-world applications.